STROKE EMERGENCY HEALTH EDUCATION IN THE COMMUNITY OF PULO NYAMUK VILLAGE - Sasmito, Priyo; Royani, Royani; Rustini, Ira; Aulia, Gina; Novena Simanjutak, Shania; Shinta Dewi, Yasmin; Robertus, Sumardi; Mutohharoh, Hopipah (CV. Alina, 2023)
The prevalence of stroke every year has increased significantly, and has become the third leading cause of disability and also the third cause of death in the world. In 2015, the World Health Organization (WHO) stated that every year there are 15 million people affected by stroke and become the leading cause of death after ischemic heart Stroke is a functional brain disorder disease in the form of paralysis of the nerves (neurological deficit) Stroke is the third cause of disability in the world due to impaired nerve function that occurs such as visual impairment, pelo speech, impaired mobility, as well as paralysis of the face and extremities. Conditions like this that cause stroke sufferers to have a high dependence on carrying out daily activities on others. (Oktarina &; Mulyani, 2020)Service activities will be carried out on October 22, 2023 in Pulo Mosquito Village Stroke health education activities are carried out at the homes of residents of Pulo Mosquito Village. The number of participants who attended was 22 people, this form of activity was carried out by the lecture method. Before starting health education activities, the community is given pre-test questions to find out the knowledge of the community about stroke. The material is delivered by lecture method using Leaflet media. Stroke health education activities are carried out at the homes of residents of Pulo Mosquito Village. The results of the post test given regarding knowledge about stroke found that the knowledge of the people of Kampung Pulo Nyamuk increased after being given counseling materials with the results of the post test value greater than the pre-test value. But it does not rule out the possibility that there are some people who have post-test values